Estimation of Health State Utility Values in Fabry Disease Using Vignette Development and Valuation - Derralynn Hughes; Andrew Lenny; Koonal Shah; Louise Longworth; Giovanna Devercelli; Olulade Ayodele (Journal of Health Economics and Outcomes Research)
**Background:** Health state utilities are measures of health-related quality of life that reflect the value placed on improvements in patients’ health status and are necessary for estimation of quality-adjusted life-years. Health state utility data on Fabry disease (FD) are limited. In this study we used vignette (scenario) construction and valuation to develop health state utilities.